The Role of Europa Nostra Awards in Conserving the Common Cultural Heritage of Cyprus - Mısırlısoy, Damla; Günçe, Ka?an (Peter Lang Publishing Group, 2023)
The Republic of Cyprus, which was established in 1960 by the partnership of Turkish Cypriots and Greek Cypriots, joined the European Union in 2004. In 1974, the island divided into two with the “Buffer Zone.” The division of the island into two different administrations emerged the political issues in the island. The island where two ethnic groups live after the division. The cultural heritage on the island, which has a rich cultural past, can be considered the common heritage of Turkish Cypriots and Greek Cypriots, and even of Europe. With the entry of the Republic of Cyprus into the European Union, the value of the cultural heritage in the whole of the island has become more noticeable by the European Union. The universal value of cultural heritage is conducive to the preservation of this heritage and its existence, and the strengthening of intercultural dialogue. There are many international organizations working for the preservation of cultural heritage. Especially in recent years, the efforts of the European Union to support and reward exemplary projects, practices, research studies on the conservation of cultural heritage draw attention. Europa Nostra is an international network of cultural heritage conservation that unites many non- governmental and management organizations across Europe, as well as members. One of the important support given by the European Union for the protection of cultural heritage is the Europa Nostra awards. Within the scope of the study, the awards received from “Europa Nostra” for the cultural heritage preservation works in the North and South of Cyprus will be examined. Award- winning projects will be handled separately, and their values and problems in terms of conservation will be revealed. Evaluations will be made as to whether these award- winning projects have an “integrative” effect on the divided island, as well as on Turkish and Greek Cypriots. In addition, the cooperation between Greek Cypriots and Turkish Cypriots of UNDP projects involving representatives of both communities for the conservation of the common cultural heritage, and the dedication shown in the conservation of cultural heritage on the island is discussed with the “Europa Nostra” awards, while the reflections of the awarded projects on inter- communal relations is questioned. The study is guided by social – cultural, economic and political readings through field study and literature study. © 2023 Peter Lang GmbH, Internationaler Verlag der Wissenschaften.
Keywords: common cultural values; conservation; cultural heritage; Cyprus; deadlock situation; Europa Nostra Awards